Dingoes - Gentle, Victor and Janet Perry (Milwaukee, WI Gareth Stevens Publishing, 2002)
An introduction to the physical characteristics and behavior of the dingo, also describing its history and impact on the ecosystem in Australia.
Keywords: Dingo